2012
DOI: 10.1002/aoc.2921
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of palladium‐catalyzed decarboxylative coupling of phenylpropiolic acid and aryl iodide

Abstract: The mechanism of decarboxylative coupling of phenylpropiolic acid and methyl 4‐iodobenzoate was investigated by gas chromatographic analysis and monitoring the decarboxylation reaction by FT‐IR spectroscopy. Among many possible pathways, we found that the mechanism involves two possible pathways, namely the decarboxylation of phenylpropiolic acid and that proceeding through the carboxylated palladium complex. Copyright © 2012 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Recently, we developed the palladium-catalyzed decarboxylative coupling reaction of alkynyl carboxylic acids and the efficient methods for the synthesis of diaryl alkynes, diynes, alkynyl ketones, and aryl propiolic acids . In the course of our effort to expand the decarboxylative coupling reactions, we found that phenyl propiolic acid was decarboxylated to produce phenyl acetylene in the absence of metal when the reaction was run with an organic base at 80 °C …”
mentioning
confidence: 99%
“…Recently, we developed the palladium-catalyzed decarboxylative coupling reaction of alkynyl carboxylic acids and the efficient methods for the synthesis of diaryl alkynes, diynes, alkynyl ketones, and aryl propiolic acids . In the course of our effort to expand the decarboxylative coupling reactions, we found that phenyl propiolic acid was decarboxylated to produce phenyl acetylene in the absence of metal when the reaction was run with an organic base at 80 °C …”
mentioning
confidence: 99%
“…This is followed by intramolecular cyclocarbopalladation to form the π-allylpalladium intermediate B, which then rapidly undergoes an exothermic inner-sphere pivalate-halide exchange. 17,20 The resulting more stable and less electron-rich η 3 -allylpalladium C is afterward involved in the decarboxylative allylic alkynylation C. To date, two possible ways for the decarboxylation of phenylpropiolic acid are considered: 21 (1) in situ decarboxylation of the propiolic acid and then the decarboxylated alkyne reacts with the palladium complex C (outer-sphere mechanism or S N 2′); 22 (2) the propiolic acid reacts with the palladium complex C to produce the phenyl propiolate palladium complex D before the decarboxylation step (inner-sphere mechanism). 23 Based on previous results observed by Grigg,3a,b the S N 2′-type attack on the (π-allyl)Pd complex, a charge-controlled outer-sphere mechanism, can be precluded because it favors an α-attack, leading to the branched product.…”
mentioning
confidence: 99%